A daily repeated measures study of job search and distress : evidence from China - Song, Zhaoli (2013)
We examined the relationship between job search and distress using the daily diary method that involved 100 unemployed job seekers in China. Three models were tested: a direct relationship model (examining the effect of job search on distress), a reversed relationship model (assessing the impact of distress on job search), and a third variable model (testing the extent to which daily financial strain accounts for the relationship between job search and distress). Results offered support for both direct and reversed models. The third variable model was not supported. Negative job search experience mediated the direct effect of job search on distress. Using a within-individual approach, our study provides an in-depth examination on the nature and directionality of the relationship between job search and distress and illuminates the dynamic nature of this relationship.